A Randomized Trial Exploring the Effect of a Telephone Call Follow‐up on Care Plan Compliance Among Older Adults Discharged Home From the Emergency Department. (February 2014) - Biese, Kevin; LaMantia, Michael; Shofer, Frances; McCall, Brenda; Roberts, Ellen; Stearns, Sally C.; Principe, Stephanie; Kizer, John S.; Cairns, Charles B.; Busby‐Whitehead, Jan; Gaddis, Gary
Abstract Objectives Older patients discharged from the emergency department (ED) have difficulty comprehending discharge plans and are at high risk of adverse outcomes. The authors investigated whether a postdischarge telephone call–mediated intervention by a nurse would improve discharge care plan adherence, specifically by expediting post–ED visit physician follow‐up appointments and/or compliance with medication changes. The second objectives were to determine if this telephone call intervention would reduce return ED visits and/or hospitalizations within 35 days of the index ED visit and to determine potential cost savings of this intervention. Methods This was a 10‐week randomized, controlled trial among patients aged 65 and older discharged to home from an academic ED. At 1 to 3 days after each patient's index ED visit, a trained nurse called intervention group patients to review discharge instructions and assist with discharge plan compliance; placebo call group patients received a patient satisfaction survey call, while the control group patients were not called. Data collection calls occurred at 5 to 8 days and 30 to 35 days after the index ED visits for all three groups. Chi‐square or Fisher's exact tests were performed for categorical data and the Kruskal‐Wallis test examined group differences in time to follow‐up. Results A total of 120 patients completed the study. Patients were 60% female and 72% white, with a mean age of 75 years (standard deviation [SD] ± 7.58 years). Intervention patients were more likely to follow up with medical providers within 5 days of their ED visits than either the placebo or the control group patients (54, 20, and 37%, respectively; p = 0.04). All groups performed well in medication acquisition and comprehension of medication indications and dosage. There were no differences in return visits to the ED or hospital within 35 days of the index ED visit for intervention patients, compared to placebo or control group patients (22, 33, and 27%, respectively; p = 0.41). An economic analysis showed an estimated 70% chance that this intervention would reduce total costs. Conclusions Telephone call follow‐up of older patients discharged from the ED resulted in expedited follow‐up for patients with their primary care physicians. Further study is warranted to determine if these results translate into improved patient outcomes, decreased return ED visits or hospital admissions, and cost savings resulting from this intervention.